Phase 2a Safety, Pharmacokinetics, and Acceptability of Dapivirine Vaginal Rings in US Postmenopausal Women. (4th October 2018) - Chen, Beatrice A; Zhang, Jingyang; Gundacker, Holly M; Hendrix, Craig W; Hoesley, Craig J; Salata, Robert A; Dezzutti, Charlene S; van der Straten, Ariane; Hall, Wayne B; Jacobson, Cindy E; Johnson, Sherri; McGowan, Ian; et al.
Abstract: Background: Postmenopausal women have unique sociobiological human immunodeficiency virus (HIV) risks. We evaluated the safety, pharmacokinetics, and acceptability of a microbicide dapivirine (DPV) vaginal ring (VR) versus placebo in postmenopausal women. Methods: We enrolled 96 HIV-negative postmenopausal US women in a phase 2a double-blind, randomized (3:1) trial of monthly VRs containing 25 mg DPV or placebo used continuously for 12 weeks. We assessed safety by adverse events (AEs). DPV concentrations were quantified in plasma and vaginal fluid. Steady-state concentrations were analyzed at 4, 8, and 12 weeks using repeated measures ANOVA. We assessed acceptability by self-report. Results: We found no differences in the proportion of women with related grade 2 or higher reproductive system AEs (DPV: 6/72 (8%), placebo: 3/24 (13%), P = .68) or grade 3 or higher AEs (DPV: 4/72 (6%), placebo: 0/24 (0%), P = .57). In the DPV arm, 2/72 (3%) declined to resume product use due to AEs. Median DPV concentrations in plasma (262.0 pg/mL at week 12) and vaginal fluid (40.6 ng/mg at week 12) were constant over 12 weeks and exceeded the in vitro 50% effective concentration by 5000-fold in vaginal fluid by week 4. VR acceptability was high; 84/93 (90%) "very much liked or liked" the VR. Conclusions: DPV VRs were safe, well tolerated, and acceptable in postmenopausal women. Plasma concentrations were comparable to published data on DPV use in reproductive-age women (median plasma concentration: 264 pg/mL). Given the reassuring safety and pharmacokinetic data, the DPV VR is promising for preexposure prophylaxis in postmenopausal women. Clinical Trials Registration: NCT02010593. Abstract : Dapivirine vaginal rings are safe, well tolerated, and acceptable in postmenopausal women with dapivirine concentrations comparable to reproductive-age women. Given the reassuring safety and pharmacokinetic data, dapivirine rings show potential as an option for HIV preexposure prophylaxis in postmenopausal women.